2020
DOI: 10.2147/jpr.s228766
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Vitellaria paradoxa</em> Nut Triterpene-Rich Extract Ameliorates Symptoms of Inflammation on Post-Traumatic Osteoarthritis in Obese Rats</p>

Abstract: Purpose: To investigate the ameliorative effects of Vitellaria paradoxa (VP) nut extract for an anterior cruciate ligament transection with medial meniscectomy (ACLT+MMx)-induced osteoarthritis (OA) in high-fat diet (HFD)-induced obese rats. Methods: The rats were fed by HFD for 5 weeks before surgery-induced OA. Rats were treated orally with three different doses of VP nut extract (111.6, 223.2, and 446.4 mg/kg) for 8 weeks. Results: The VP nut triterpene-rich extract decreased the level of triglycerides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
(61 reference statements)
2
9
0
Order By: Relevance
“…It is worth noting, a reduction of body weight was also observed in SNO and SNOHA treated rats. This similar finding was reported recently in obese rats [29]. The anti-obesity effect of SNO could be the result of reduction of OA pain, or vice versa.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is worth noting, a reduction of body weight was also observed in SNO and SNOHA treated rats. This similar finding was reported recently in obese rats [29]. The anti-obesity effect of SNO could be the result of reduction of OA pain, or vice versa.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the potential antioxidant and free radical scavenging effects of amyrin and lupeol have been demonstrated both in vitro and in vivo [25][26][27][28]. A recent report showed increased antioxidant activity and suppressed proinflammatory cytokine expressions in obese OA rats fed with SNO, further consolidating our previous findings [29]. Either of the triterpenoids and their potential target mechanisms may play a key regulatory role in our OA model and contribute to the antiarthritic action of SNO.…”
Section: Introductionsupporting
confidence: 72%
“…Triterpene alcohols such as α-amyrin, β-amyrin, lupeol, and butyrospermol, most of which occur as acetyl and cinnamyl ester derivatives, have been previously reported to be the main non-glyceride constituents of V. paradoxa kernel [ 5 , 6 , 15 , 16 ], leaves [ 17 ], and stem bark [ 4 , 10 , 18 ] extracts. Typically, the kernel fat contains ca.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have demonstrated that the anti-inflammatory activity of stem bark extracts is mainly ascribed to their rich triterpenoid composition [ 4 ], which have been proposed to act by inhibiting pro-inflammatory cytokines and iNOS and COX-2 expression [ 5 ]. Recently, a V. paradoxa triterpene-rich extract was shown to suppress pro-inflammatory mediators and attenuate the cartilage degradation and pain in osteoarthritis in an obesity rat model [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herbal compounds with cartilage protective, antiinflammatory, antioxidant, and antimatrix-degrading effects have also been widely used for the treatment of OA (He et al, 2020;Mobasheri, 2012;Sudirman et al, 2020). In a previous report in a mouse model of OA, 50 mg/kg F I G U R E 5 Effect of puerarin on IL-1β, IL-6 and TNF-α inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%